Project Based Learning: Peningkatan Hasil Belajar Peserta Didik pada Materi Jenis Wiwaha Menggunakan Media Canva di SMA Negeri 1 Basarang - KT. Maryani Anjasmari (Jurnal Pendidikan Madrasah, 2023)
This study aims to improve the learning outcomes of students on wiwaha type material through a project based learning (PjBL) model with Canva media. This research design uses a quasi-experimental research design (pseudo-experiment). The population in this study was all grade XI students of SMAN 1 Basarang, while the sample was grade XI-1 students. Data was collected through observation and provision of test questions in the form of pre-test and post-test questions. Data analysis techniques use quantitative data analysis. From the results of the study, student learning results were obtained on the wiwaha type material after being taught using a PjBL model using Canva media, a percentage of 100% of students achieved KKM scores. The increase in student learning outcomes is in line with the increase in student activity with a percentage of 85%. Thus, the PjBL model with Canva media is able to improve student learning outcomes on wiwaha type material, also having a positive impact on student activities.